DETERMINANTS OF INTERNET DISCLOSURE TRANSPARENCY ON ZAKAT MANAGEMENT ORGANIZATIONS IN INDONESIA - Khomsatun, Siti; Fikry, Rifqi Roushan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
This study's purpose is to examine the influence of Zakat Management Organization (OPZ) characteristics on the transparency of Internet disclosure. There are four independent variables such as the size of OPZ, the presence of external auditors, under the auspices of the corporation status, and institution type. The size of OPZ is measured by the ln of the total assets, whereas the existence of the external auditor, the auspices of the corporation status, and the type of institution use dummy variables. The sample of this research is 32 OPZ in Indonesia with the research period 2018. The results show that the size of OPZ, the presence of auditors, and the ownership status of the institution had a significant positive effect on the transparency of Internet disclosure. However, the type of institution (BAZ or LAZ) does not affect the transparency of internet disclosure at OPZ. The percentage of disclosure of internet disclosures, such as content and presentation on the OPZ website, has increased from previous studies.